Emotional security - Catherine Ann Cameron (2018)
© Palgrave Macmillan, a division of Macmillan Publishers Limited 2014. Juanita is tending a doll and stuffed rabbit that her aunt Lina has given her, with accompanying blankets, a ‘manta’ or colourfully woven cloth in which Peruvian mothers carry their babies, and a basket as staging for make-believe baby-minding, while Lina and the other adult female family members attend to routine household duties.